2021
DOI: 10.3390/jcm10020278
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on In-Hospital Outcomes of ST-Segment Elevation Myocardial Infarction Patients

Abstract: Primary percutaneous coronary intervention (PPCI) is one of the important clinical procedures that have been affected by the COVID-19 pandemic. In this study, we aimed to assess the incidence and impact of COVID-19 on in-hospital clinical outcome of ST elevation myocardial infarction (STEMI) patients managed with PPCI. This observational retrospective study was conducted on consecutive STEMI patients who presented to the International Cardiac Center (ICC) hospital, Alexandria, Egypt between 1 February and 31 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…A total of 32 studies met our inclusion criteria. Four studies each originated from China, 4,24,32,33 Italy, 20,[34][35][36] and North America, [37][38][39][40] 3 each from France [41][42][43] and Turkey, [44][45][46] 2 from the United Kingdom, 47,48 and 1 each from Austria, 49 Belgium, 50 Egypt, 51 Iran, 52 Israel, 53 Japan, 54 Pakistan, 55 Poland, 56 Singapore, 23 Spain, 57 and Switzerland. 60 One study was a multicentred cohort study of various databases belonging to different European countries.…”
Section: Summary Of Included Studiesmentioning
confidence: 99%
“…A total of 32 studies met our inclusion criteria. Four studies each originated from China, 4,24,32,33 Italy, 20,[34][35][36] and North America, [37][38][39][40] 3 each from France [41][42][43] and Turkey, [44][45][46] 2 from the United Kingdom, 47,48 and 1 each from Austria, 49 Belgium, 50 Egypt, 51 Iran, 52 Israel, 53 Japan, 54 Pakistan, 55 Poland, 56 Singapore, 23 Spain, 57 and Switzerland. 60 One study was a multicentred cohort study of various databases belonging to different European countries.…”
Section: Summary Of Included Studiesmentioning
confidence: 99%
“…Most previous studies have suggested longer total ischemia time and time from first medical contact do angiography in patients admitted during COVID-19 pandemic [1,25,29]. Furthermore, some investigators have also demonstrated an escalated risk of death and adverse events [8,25,29]. However, retrospective nature without balanced rate of risk factors and low sample size might limit the generalizability of these studies.…”
Section: Discussionmentioning
confidence: 94%
“…Pandemicspecific protocols for preparing personal protective equipment and obligatory COVID-19 testing consume additional time and extend the time for reperfusion [1][2][3][4]10,12]. Most previous studies have suggested longer total ischemia time and time from first medical contact do angiography in patients admitted during COVID-19 pandemic [1,25,29]. Furthermore, some investigators have also demonstrated an escalated risk of death and adverse events [8,25,29].…”
Section: Discussionmentioning
confidence: 99%
“…Our hospital admission analysis showed a trend toward a reduction in acute coronary syndromes incidence, with a substantial increase in STEMI fatality rate and complications during the pandemic, compared with 2019 [8]. This was explained by the decrease in percutaneous coronary intervention (PCI) procedures [9], with an annual 634 PCI patients falling by 25.7% during the COVID-19 period (mean 30.0 ± 4.01 vs. 40.4 ± 5.3 case/month) and prolongation of the time from first medical contact to needle (125.0 ± 53.6 vs. 52.6 ± 22.8 min, p = 0.001). Such significant change in practice was interpreted on the basis of patients' fear of visiting the hospital, lack of organized emergency pathways for acute coronary syndromes during the COVID-19 period, and occasional misdiagnosis in patients with respiratory symptoms.…”
mentioning
confidence: 77%